Improving Students Activitivy And Students Achievement In Learning Pkn By Using Role Play Strategy At The Tenth Grade Students Of Sma Eka Sakti Padang - Syafrial Syafrial (Jurnal Ilmiah Pendidikan Scholastic, 2018)
This research is based on the activity of formulation of PPKN problem through role playing strategy at the tenth grade students of SMA Eka Sakti Padang, and implementation and assessment of KDPN learning that can improve learning result with role playing strategy at the tenth grade students of SMA Eka Sakti Padang,. Based on the data processing and discussion conducted, the results obtained at cycle time 6.96 and increased in cycle II through 8.57. The research method used is classroom action research (classroom action research). Based on the results of the study, it can be concluded that the successful implementation of research that has been done in SMA Eka sakti Padang. Based on the results of the study, it can be concluded that there is an increase in student learning outcomes of grade tenth in SMA Eka sakti Padang significant on learning PPKN by using role playing strategy.